Bioactive Compounds Isolated and Characterized from Ocimum Sanctum Leaves in Antidiabetic - Shubhee Yadav,; Sangeeta Singh, (American Journal of Biology and Natural Sciences, 2025)
Diabetes mellitus is a significant global health concern, driving the search for effective natural therapeutic agents with fewer side effects than conventional drugs. Ocimum sanctum L., commonly known as Holy Basil or Tulsi, has shown promising antidiabetic properties in traditional medicine and scientific studies. This research focuses on the bioactivity-guided isolation and characterization of the specific compounds within O. sanctum leaves responsible for its blood glucose-lowering effects.